Effects of aqueous and ethanolic extracts of Chinese propolis on dental pulp stem cell viability, migration and cytokine expression - Park,Ha Bin; Dinh,Yen; Yesares Rubi,Pilar; Gibbs,Jennifer L.; Michot,Benoit (PeerJ, 2024)
Background Propolis is a natural substance produced by honeybees that has various biological properties including, anti-inflammatory, antioxidant and antimicrobial properties. Although previous studies have evaluated the antimicrobial effects of propolis in dentistry, its effects on dental pulp stem cell (DPSC) viability, migration, and differentiation are yet not well understood. The objective of this study was to investigate the effects of Chinese propolis on viability/proliferation, migration, differentiation and cytokine expression in DPSCs. Methods Commercially available DPSCs (Lonza) were treated with aqueous extract of propolis (AEP) or ethanolic extract of propolis (EEP), and viability/proliferation was evaluated using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assays and quantification of nuclear staining. DPSC differentiation into mineralizing cells was evaluated with Alizarin red staining and cell migration was assessed using Boyden Chamber Transwell inserts. Cytokine expression was measured by RT-qPCR. AEP and EEP at 0.03 and 0.1 mg/mL did not affect DPSC viability/proliferation for up to 7-days treatment. Results Higher doses (0.33–33 mg/mL) induced a dose dependent decrease in DPSC viability/proliferation with a more prominent effect with EEP at 7 days. Neither AEP nor EEP induced DPSC differentiation into mineralizing cells, but both AEP and EEP (0.03–0.1 mg/ml) induced a dose dependent increase in DPSC migration. In addition, EEP prevents the upregulation of IL1b and IL6 but not IL8 and CCL2 in response to lipopolysaccharide stimulation. AEP has less potent anti-inflammatory effects and prevents only IL1b upregulation. Conclusion This study provides new information about the biologic properties of ethanolic and aqueous extracts of propolis and shows that propolis, at doses that do not affect cell viability, induces DPSC migration and has anti-inflammatory properties. These data highlight the potential use of propolis as an alternative intra-canal medicament for regenerative endodontic procedures.
Keywords: Propolis; Regenerative endodontics; Dental pulp; Stem cells; Cell movement; Cytokines